Eating for Two? Protocol of an Exploratory Survey and Experimental Study on Social Norms and Norm-Based Messages Influencing European Pregnant and Non-pregnant Women’s Eating Behavior - Bevelander, Kirsten E.; Herte, Katharina; Kakoulakis, Catherine; Sanguino, Inés; Tebbe, Anna-Lena; Tünte, Markus R. (Frontiers in Psychology, 2018)
The social context is an important factor underlying unhealthy eating behavior and the development of inappropriate weight gain. Evidence is accumulating that powerful social influences can also be used as a tool to impact people’s eating behavior in a positive manner. Social norm-based messages have potential to steer people in making healthier food choices. The research field on nutritional social norms is still emerging and more research is needed to gain insights into why some people adhere to social norms whereas others do not. There are indications stemming from empirical studies on social eating behavior that this may be due to ingratiation purposes and uncertainty reduction. That is, people match their eating behavior to that of the norm set by their eating companion(s) in order to blend in and be part of the group. In this project, we explore nutritional social norms among pregnant women. This population is particularly interesting because they are often subject to unsolicited advice and experience social pressure from their environment. In addition, their pregnancy affects their body composition, eating pattern and psychosocial status. Pregnancy provides an important window of opportunity to impact health of pregnant women and their child. Nevertheless, the field of nutritional social norms among pregnant women is understudied and more knowledge is needed on whether pregnant women use guidelines from their social environment for their own eating behavior. In this project we aim to fill this research gap by means of an exploratory survey (Study 1) assessing information about social expectations, (mis)perceived social norms and the role of different reference groups such as other pregnant women, family and friends. In addition, we conduct an online experiment (Study 2) testing to what extent pregnant women are susceptible to social norm-based messages compared to non-pregnant women. Moreover, possible moderators are explored which might impact women’s susceptibility to social norms as well as cultural aspects that co-determine which social norms and guidelines exist. The project’s findings could help design effective intervention messages in promoting healthy eating behavior specifically targeted to European pregnant women.